WOUND HEALING POTENTIAL OF METHANOL EXTRACT OF SPATHODEA CAMPANULATA STEM BARK FORMULATED INTO A TOPICAL PREPARATION - Ofori-Kwakye, K.; Kwapong, A. A.; Bayor, M. T. (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
This study evaluated the wound healing potential of Spathodea campanulata stem bark in Sprague Dawley rats using the excision wound model. The methanol extract contained glycosides, flavonoids and tannins, and was relatively stable when stored at the room temperature for six (6) months. Solvent-free, semi-solid extract of S. campanulata was incorporated into an aqueous cream and applied (10 % w/w and 20 % w/w) on excision wounds of thirty two (32) rats. Cicatrin® cream was used as a standard wound healing agent. Prior to the remedial cream application, done later on twice daily, sixteen (16) rats had their wounds infected with Staphylococcus aureus, while in the remaining sixteen the wounds were kept clean. The surface area of the excision wounds was monitored planimetrically every four (4) days until a complete wound closure or healing took place. Excision wounds treated with 20 % w/w Spathodea cream and Cicatrin® cream showed a rapid and comparable decrease (p > 0.05) in wound size. In uninfected wounds, both 20 % w/w Spathodea cream and Cicatrin® cream application resulted in 95 %-wound closure seen on Day 20, and a complete closure seen on Day 24. In infected wounds, both 20 % w/w Spathodea cream and Cicatrin® cream administration led to 91 %-wound closure on Day 24 and a complete wound contraction on Day 28. The results of this study justify the folkloric use of S. campanulata stem bark to the effect of wound treatment.